Royal spin : a novel - Scobie, Omid; Benway, Robin (William Morrow, 2026)
"Emily in Paris meets Veep meets Red, White and Royal Blue in this sparkling fish-out-of-water romantic workplace comedy about a young American who trades a job at the White House for one at Buckingham Palace, from the dream writing duo: preeminent royal correspondent Omid Scobie and National Book Award-winner Robin Benway, both beloved New York Times bestselling authors"-- Provided by publisher.